Students' Learning Experiences With LMS Tes Teach In Flipped-Class Instruction - Zainuddin, Zamzami; Hermawan, Hardika Dwi; Nuraini, Febritesna; Prayitno, Santo Mugi (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2019)
The purpose of this study was to identify the impact of implementing a Learning Management System (LMS)